Urinary and oral microbiota in Polish women: a pilot case-control study of breast cancer - Marciniak, Anna; Skrzypczak-Zielińska, Marzena; Zakerska-Banaszak, Oliwia; Nowakowska, Elżbieta; Kozaczka, Anna; Zemła, Brunon; Szpak, Andrzej; Godlewski, Dariusz; Charzewska, Jadwiga; Pathak, Dorothy R. (Frontiers in Microbiology, 2025)
IntroductionThe human microbiota can be a critical component in the development and progression of various diseases, including cancer. This study aims to investigate the composition of the urinary and oral microbiota in Polish breast cancer (BC) patients relative to healthy controls (HCs) and to predict relevant metabolic pathways of microbiota in studied groups.MethodsUrine and oral samples from 48 participants, 24 BC cases and 24 HCs, randomly selected from 417 BC cases and 514 HCs, were analyzed using next-generation sequencing of bacterial 16S rRNA gene (V1-V9) and fungal ITS regions, along with bioinformatics tools to identify and compare microbial communities and predict relevant pathways of microbiota in the studied groups.ResultsBC case urine microbiota contained an increased abundance of Corynebacterium (5.2-fold, but not significant) and Gammaproteobacteria including unknown genus and Pseudomonas (1.7- and 1.8-fold) and decreased abundance of Family XI (0.3-fold) and Bifidobacteriaceae (0.4-fold) compared to HCs. Oral BC microbiota contains higher levels of the bacterial families P5D1–392, Leptotrichiaceae, and Pasteurellaceae (3.3-, 3.3-, and 1.9-fold, respectively), whereas the genera Cellulosimicrobium, Pseudomonas, and Pantoea were significantly less abundant (0.4-, 0.3-, and 0.3-fold, respectively). At the species level, the most differentiating species between BC and HC was uncultured Pseudomonas sp. (1.8-fold) in urine and Pantoea agglomerans (0.2-fold) in oral microbiota. Fungal composition did not show any significant differences between the groups. Functional analysis based on Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt2) predicted, e.g. enhanced hydrogen production and benzoyl-CoA degradation in BC cases, as well as reduced CMP-diacetamido-8-epilegionaminic acid biosynthesis.DiscussionThe study underscores the potential significance of the microbiota in BC pathogenesis. Further research is needed to elucidate the mechanisms underlying microbiota–tumor interactions and to explore the clinical applications.